Biogenic synthesis of silver nanoparticles using methanolic extracts of Ulva lactuca: GC/MS analysis, antibacterial, antioxidant, and antidiabetic activity - N.V. Mrunalini; P. Naga Deepthi; B. Kishori; S.B. Sainath (Next Materials, 2025)
In this study, we aimed at biogenic synthesis of silver nanoparticles (NPs) based methanolic extracts of marine macro-algae, Ulva lactuca and to evaluate the antibacterial, antifungal, antioxidant and antidiabetic effects of green synthesized silver-NPs. The biosynthesized silver-NPs showed maximum absorption between 395 nm to 400 nm in the UV–visible spectrum. X-ray diffraction and Scanning electron microscopy analyses revealed that the synthesized silver-NPs were spherical in shape. Fourier transmission infrared measurements indicated that the methanolic extracts of U. lactuca comprised of bioactive groups accountable for the reduction of silver ions, suggesting occurrence of capping agents and provided stability to the synthesized silver-NPs. GC-MS analysis revealed several bioactive compounds in the methanolic extracts of U. lactuca and most notably we noticed diterpenoid like Neophytadiene. Following the characterization studies, the synthesized silver-NPs were analyzed for its antimicrobial, antioxidant and anti-diabetic abilities. Interestingly, biogenic silver-NPs exhibited antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, but did not elicit antifungal activity against Candida albicans and Aspergillus niger at selected concentrations. Synthesized silver-NPs using methanolic extracts of U. lactuca exhibited (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity, superoxide and hydroxy radicals scavenging activity and hydrogen peroxide scavenging activity suggesting antioxidant potential. Further, Phyto synthesized silver NPs also showed antidiabetic activity in vitro as indicated by alpha-glucosidase inhibitory assay. Based on the bioactivity of synthesized silver NPs using methanolic extracts of U. lactuca, it might be used in clinical use as an antibacterial, antioxidant and antidiabetic agent.